PRAKTEK JUAL BELI “SEROK LIVE” TIK TOK SHOP DALAM TINJAUAN EKONOMI ISLAM - Syamratun Nurjannah; Reni Helvira; Ari Widiati (Ar-Ribhu : Jurnal Manajemen dan Keuangan Syariah, 2023)
This study discusses the Practice of Serok Live Buying and Selling Islamic Economics’ Review. Buying and selling are generally defined as the process of exchanging goods or services between sellers and buyers. Along with the developing era, they were marked by many changes in various aspects of life, from manual to application. The same things happened for buying and selling activities. TikTok is an application used to create and share different short recordings within a vertical organization. As technology develops, TikTok issued two features which are used in buying and selling, such as the Tiktok shop and buying and selling via Live Streaming. The purpose of this research is to find out the practice of buying and selling using the TikTok shop "Serok Live" model, as well as to find out an Islamic economics’ review of the buying and selling "Serok Live" of TikTok shop practice. The research method used in this study is a qualitative approach. This means that the data collected was not in the form of numbers, but it came from interview scripts, field notes, personal documents, notes, memos and other official documents. So this research intends to understand the phenomenon of what is experienced by research subjects in forms of perception, behaviour, action, motivation, etc as well as in a descriptive way in forms of words and language by utilizing various scientific method. The results of the study showed that the buying and selling of this Serok Live system contained an element of uncertainty in the amount of goods being traded. This was because the goods sold were taken in batches, so that each buyer might get a different amount of goods at the same cost. This, of course, makes the buyers loss. Besides, the sellers can also experience a loss, because the goods which are scooped up are not suitable with the capital that has been issued. This can be seen during the live process, it is not uncommon for sellers to exchange items that have been checked out, for various reasons. This usually happens when it turns out that there are two types of goods which prices are included in the premium category. So actually the seller himself has arranged so that the goods which are scooped up do not exceed the capital that has been issued. Keywords : Buying and Selling, TikTok, Serok Live, Islamic Economics Review.